Strategic plan to improve professional skills in English inside commercial areas of Colombian companies, based on autonomous learning (2014)
This research project establishes a complete proposal of a strategic plan which pretends to be a tool for learning English in autonomous ways, specifically applied in commercial areas from Colombian companies, using as diagnosis structure a SWOT analysis (Strengths, Weaknesses, Opportunities and Threats), used in lots of companies because of its high effectiveness level related to strategic results; in fact this method accurately allows to identify which factors permit and which other affect an English learning process, especially when are involved self-directed and autonomous methodologies, those have bigger risks of dropping out the English courses than traditional studying methods. This research as well pretends to improve the commercial procedures highlighting the importance of English and intercultural communication during international trade agreements. In addition; this project uses as basis some of the internationalization proposals established by government, some governmental organizations and the company used for finding out the need of interpreting English inside the commercial area.